Adenosine thiamine triphosphate and adenosine thiamine triphosphate hydrolase activity in animal tissues - A. F. Makarchikov; T. V. Saroka; T. G. Kudyrka; I. K. Kolas; T. A. Luchko; I. M. Rusina; V. A. Gurinovich (The Ukrainian Biochemical Journal, 2018)
Adenosine thiamine triphosphate (AThTP), a vitamin B1 containing nucleotide with unknown biochemical role, was found previously to be present in various biological objects including bacteria, yeast, some human, rat and mouse tissues, as well as plant roots. In this study we quantify AThTP in mouse, rat, bovine and chicks. We also show that in animal tissues the hydrolysis of AThTP is catalyzed by a membrane-bound enzyme seemingly of microsomal origin as established for rat liver, which exhibits an alkaline pH optimum of 8.0-8.5 and requires no Mg2+ ions for activity. In liver homogenates, AThTP hydrolase obeys Michaelis-Menten kinetics with apparent Km values of 84.4 ± 9.4 and 54.6 ± 13.1 µМ as estimated from the Hanes plots for rat and chicken enzymes, respectively. The hydrolysis of AThTP has been found to occur in all samples examined from rat, chicken and bovine tissues, with liver and kidney being the most abundant in enzyme activity. In rat liver, the activity of AThTP hydrolase depends on the age of animals.